2001
DOI: 10.2113/gscanmin.39.2.331
|View full text |Cite
|
Sign up to set email alerts
|

The Valence and Speciation of Sulfur in Glasses by X-Ray Absorption Spectroscopy

Abstract: The geochemical behavior of sulfur in magmas depends strongly on the oxidation state of sulfur, but this is not easily determined by standard analytical methods. We have measured XANES absorption spectra at the sulfur K-edge and have found that such measurements are useful to characterize the oxidation state and speciation of sulfur in silicate glasses of geological relevance. Measured spectra of a set of reference minerals show the effects of different oxidation states and coordination numbers of sulfur; ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 31 publications
8
51
0
Order By: Relevance
“…The S K-and L-edge spectra (Figs. 2, 13, 14; Li et al 1995a, Kasrai et al 1996b) exhibit a progressive increase in the energy position of the edge feature with increase in oxidation state, refl ecting the progressive increase in charge on the absorber atom, to maximum values of 2482 eV and about 171 eV, respectively, for divalent metal sulfates, although Paris et al (2001) reported a value of 2483.1 eV for the Kedge peak of sulfate in a natural apatite. In Figure 13, which is after Li et al (1995a), the K and L edges of the sulfates MgSO 4 •2H 2 O, gypsum (CaSO 4 •2H 2 O), anhydrite, celestine and barite are correlated on a common energy-scale using the S K␣ 1 X-ray emission energy at 2307.8 eV and the S 1s binding energy for Kedge spectra and the S 2p 3/2 binding energy for L-edge spectra.…”
Section: Oxyanions Of Sulfurmentioning
confidence: 99%
See 4 more Smart Citations
“…The S K-and L-edge spectra (Figs. 2, 13, 14; Li et al 1995a, Kasrai et al 1996b) exhibit a progressive increase in the energy position of the edge feature with increase in oxidation state, refl ecting the progressive increase in charge on the absorber atom, to maximum values of 2482 eV and about 171 eV, respectively, for divalent metal sulfates, although Paris et al (2001) reported a value of 2483.1 eV for the Kedge peak of sulfate in a natural apatite. In Figure 13, which is after Li et al (1995a), the K and L edges of the sulfates MgSO 4 •2H 2 O, gypsum (CaSO 4 •2H 2 O), anhydrite, celestine and barite are correlated on a common energy-scale using the S K␣ 1 X-ray emission energy at 2307.8 eV and the S 1s binding energy for Kedge spectra and the S 2p 3/2 binding energy for L-edge spectra.…”
Section: Oxyanions Of Sulfurmentioning
confidence: 99%
“…The energy position of the S K edge decreases almost linearly with increase in the number of 3d electrons, by about 1 eV from Ca 2+ to Zn 2+ . SILICATE GLASSES Paris et al (2001) used S K-edge XANES spectroscopy to study the speciation of S in some natural and synthetic glasses of basaltic to rhyolitic compositions and S contents of 0.045 to 0.30 wt.%. Spectra for a back-arc basalt, three samples of dacite from Mt.…”
Section: Oxyanions Of Sulfurmentioning
confidence: 99%
See 3 more Smart Citations